2018
DOI: 10.12659/msm.909915
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Use of Kinesio Taping Method on the Reduction of Swelling in Patients After Orthognathic Surgery: A Pilot Study

Abstract: BackgroundOrthognathic surgery (OGS) is associated with extensive surgical intervention within the soft and hard tissues of the facial region of the skull leading to inflammatory reactions. The presence of postoperative swelling indicates the accumulation of exudate or transudate; both these fluids occur in surgery. Massive swelling is a significant problem, because the tension of tissues intensifies pain sensations. The aim of the study was to evaluate the effectiveness of the kinesio taping method (KT) in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 61 publications
2
23
0
3
Order By: Relevance
“…Two studiesnot included in this review due to the lack of control group in one and the lack of detailed information from a conference abstract in the other-state a benefit of kinesiotape application after penile surgery [28,29], emphasizing the advantageous versatility of the technique that is adaptable to various anatomic regions. One additional study that lacked a control group and was therefore equally excluded in this review concludes a benefit of kinesiotaping after orthognatic surgery for the reduction of postoperative swelling [30]. Fig.…”
Section: The Broader Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studiesnot included in this review due to the lack of control group in one and the lack of detailed information from a conference abstract in the other-state a benefit of kinesiotape application after penile surgery [28,29], emphasizing the advantageous versatility of the technique that is adaptable to various anatomic regions. One additional study that lacked a control group and was therefore equally excluded in this review concludes a benefit of kinesiotaping after orthognatic surgery for the reduction of postoperative swelling [30]. Fig.…”
Section: The Broader Contextmentioning
confidence: 99%
“…Considering extremity surgery, manual lymphatic drainage is broadly accepted for the treatment of postoperative and posttraumatic oedema [31][32][33] as well as oedema caused by other pathologies [2,29,30], even though corresponding evidence is conflicting [3,4,34,35]. The application of pneumatic compression was also established as treatment option [36][37][38], although again with limited evidence base [38][39][40][41].…”
Section: The Broader Contextmentioning
confidence: 99%
“…Postoperative swelling, pain, and limitation of mouth opening are common after impacted third molar surgeries and severely decrease the patients’ quality of life. Despite the increased clinical application of KT in physiotherapy practice, especially after traumatic injuries, only a few studies investigate the effectiveness of KT in OMS literature; two studies showing effects of KT after maxillofacial trauma, 17 , 19 four studies after impacted tooth surgery, 5 , 15 , 16 , 18 two studies after orthognathic surgery, 20 , 21 and one study for temporomandibular joint disorders. 23 However, the aforementioned studies did not include placebo taping.…”
Section: Discussionmentioning
confidence: 99%
“…Genc, et al 5 (2019) compared the effectiveness of KT and surgical drain on postoperative morbidity after third molar surgery, observing significantly greater swelling and pain in KT group, and comparable occurrence of trismus in both groups. Lietz-Kijak, et al 21 (2018) revealed that KT had beneficial effects on the reduction of facial swelling after orthognathic surgery. Coskun Benlidayi, et al 23 (2016) investigated the efficacy of KT in patients with TMD regarding functional jaw movements, pain scores for joint and masticatory muscles, and depression and disability scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation